Sustainability analyses of photovoltaic electrolysis and magnetic heat engine coupled novel system used for hydrogen production and electricity generation. (August 2022) - Açıkkalp, Emin; Altuntas, Onder; Caliskan, Hakan; Grisolia, Giulia; Lucia, Umberto; Borge-Diez, David; Rosales-Asensio, Enrique
Graphical abstract: Highlights: Novel solution about photovoltaic electrolysis and magnetic heat engine is presented. Results show that the magnetic field improve the hydrogen production. Research analyses how low-temperature heat can be harvested by magnetic heat engine. The considered novel system has greater energy and exergy efficiencies at 7.6 T. Whole energy input cannot be converted to electricity due to their ineffectiveness. Abstract: In this study, energy and exergy based approaches, supported sustainability/ analyses, are applied to the photovoltaic (PV) electrolysis and magnetic heat engine, coupled novel system used for hydrogen production and electricity generation. The results point out that the magnetic field does not only improve the hydrogen production, but also low-temperature heat can be harvested by magnetic heat engine, and relatively more efficient electricity can be generated, in comparison to other harvesters. Magnetic heat engine reaches its maximum power output at 7.6 T and it is 5.53 W at this point. Energy and exergy efficiencies of the considered system are around 8% at 7.6 T, besides, it is assumed sustainable, at this value. Although the lost power is relatively higher, it can be tolerable because of unconsumable nature of the solar energy. In addition, it shows that most of energy input cannot be converted to electricity because of their ineffectiveness.